2001
DOI: 10.1161/01.hyp.38.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Mediated Effects of Bromocriptine on Cardiac Sympathovagal Balance

Abstract: Abstract-Bromocriptine, a dopamine agonist, is known to lower cardiovascular mortality in L-dopa-treated patients withParkinson's disease, probably by reducing the cardiac sympathetic activity. We aimed at unmasking the central effects of bromocriptine on the heart by power spectrum analysis. Ten healthy subjects (aged 31Ϯ2 years) in supine and sitting positions were evaluated after the administration of bromocriptine (2.5 mg) alone and after pharmacological peripheral D 2 -like blockade by domperidone (20 mg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 38 publications
5
30
0
1
Order By: Relevance
“…The results in this study are supported by enhanced dopaminergic activity during meditation (Kjaer et al, 2002). In addition, an increase in slow alpha power after administration of dopamine-releasing drugs (Ferger et al, 1996;Stahl et al, 1997) and inhibitory effects of dopamine agonists on sympathetic activity (using HRV as an index) (Franchi et al, 2001;Schobel et al, 1995) have been reported. Our results, together with these findings, suggest that internalized attention enhanced by meditation activates slow alpha power in the frontal area and inhibits sympathetic activity, and the degree of these effects is associated with the degree of NS (which, as noted, has been suggested to be associated with dopaminergic activity).…”
Section: Discussionsupporting
confidence: 76%
“…The results in this study are supported by enhanced dopaminergic activity during meditation (Kjaer et al, 2002). In addition, an increase in slow alpha power after administration of dopamine-releasing drugs (Ferger et al, 1996;Stahl et al, 1997) and inhibitory effects of dopamine agonists on sympathetic activity (using HRV as an index) (Franchi et al, 2001;Schobel et al, 1995) have been reported. Our results, together with these findings, suggest that internalized attention enhanced by meditation activates slow alpha power in the frontal area and inhibits sympathetic activity, and the degree of these effects is associated with the degree of NS (which, as noted, has been suggested to be associated with dopaminergic activity).…”
Section: Discussionsupporting
confidence: 76%
“…The observed COMT ϫ job strain interaction is in line with previous research implying that COMT genotype may affect dopamine transmission (Val/Val genotype leading to lower dopamine levels) and that dopamine may downregulate cardiac sympathetic activity and hypothalamic-pituitary-adrenal axis activity. 15,18 Our results are also in line with the evidence suggesting that dopaminergic activity could moderate the effects of stress on CHD risk factors. 14 Furthermore, our results could be explained by possibly higher subjective load in Val/Val genotype induced by their lower cognitive performance especially in tasks demanding higher order executive processes 30 and attentional control 31 that are essential in higher mental abilities.…”
Section: Discussionsupporting
confidence: 90%
“…Although not measured in the safety trial, reductions in postprandial FFA levels have been observed in other trials with bromocriptine (30,31). In animal studies, bromocriptine has been shown to attenuate the effect of CNS sympathetic overactivity on the vasculature (44,45), and a direct inhibitory effect of bromocriptine on mitogen-stimulated proliferation of rat vascular muscle cells and human aortic smooth muscle cells has been demonstrated in vitro (46). In the high fat–fed, spontaneously hypertensive rat (SHR)—an animal model of the insulin resistance syndrome and eNOS uncoupling—bromocriptine reduced pathologically elevated endothelial nitric oxide synthase (eNOS) and inducible NOS (iNOS) levels (47).…”
Section: All-cause Safety Trialmentioning
confidence: 99%